HBR guide to persuasive presentations - Duarte, Nancy (Boston Harvard Business Review Press, 2012)
Terrified of speaking in front of a group? Or simply looking to polish your skills? No matter where you are on the spectrum, this guide will give you the confidence and the tools you need to get results.
Includes index.
Keywords: Business presentations